Environmental monitoring and disease detection of plants in smart greenhouse using Internet of Things - Khan, Fazeel Ahmed; Ibrahim, Adamu Abubakar; Zeki, Akram M. (IOP Publishing, 2020)
This research implements the idea of automation using Internet of Things (IoT) in a greenhouse environment. The development is focuses on deployment of agicultural greenhouses into small-scale level transforming it into a smart greenhouse. They are to help in monitoring the greenhouse environment conditions, water irrigation management, image collection using installed cameras as well as predicting diseases in the plants on collected leaf datasets. This research focus on development for the purpose of validating a proposed system design and architecture for a suitable IoT based monitoring for environment conditions, managing water irrigation system and a effective method for detecting leaf diseases on the plants inside a greenhouse environment.